PROMOSI DAN EDUKASI PRODUK BAMBU KREATIF MELALUI MARKETING CHANNEL - Susanti, Santi; Mogot, Yuni (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2024)
Bamboo is a versatile natural resource in Indonesia that serves multiple purposes. One of the benefits is made into creative bamboo products for the needs of human life. Promotion is an important part of marketing the innovative products produced by Studio Dapur. For this purpose, Studio Dapur utilizes available marketing channels. This research aims to reveal creative bamboo products' promotion and education strategies through available marketing channels. We used a qualitative research method with a case study approach. Data was collected through interviews, observation, and documentation review in images and text. The results showed that Studio Dapur uses offline marketing channels, in the form of exhibitions, to gain networks from domestic and foreign buyers and online marketing channels, such as websites, social media, and e-commerce. The online marketing channel contains information about Studio Dapur, the products produced, and education about bamboo and its utilization as a modern product for good quality household needs.